How to identify reconnecting current sheets in incompressible Hall MHD turbulence. Issue 7 (29th July 2013) - Donato, S.; Greco, A.; Matthaeus, W. H.; Servidio, S.; Dmitruk, P.
Abstract : [1] Using high Reynolds number simulations of two‐dimensional Hall magnetohydrodynamics (HMHD) turbulence, a statistical association between magnetic discontinuities and magnetic reconnection is demonstrated. We find that sets of discontinuities, identified using the normalized partial variance of vector increments (PVI method), strongly depend on threshold in PVI statistic that is used as an identifying condition and on the strength of the Hall term. The analysis confirms that the Hall term plays an important role in turbulence and it affects the methods employed for detection of reconnecting current sheets. In particular, we found the following: (1) Among all the discontinuities detected by the PVI method, the reconnecting ones are on average thinner. (2) A reduction in size of all discontinuities and of reconnecting current sheets is observed as the threshold θ grows. (3) The average width of the reconnecting current sheets decreases as the strength of the Hall term grows and the ion inertial scale d i increases with respect to the dissipative scale. Key Points: The importance of the Hall term increating small scale current sheets PVI discovers parts next to current sheets where accelerated particles are found Statistical association between discontinuities and reconnection is demonstrated